2017
DOI: 10.12816/0042859
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Antioxidant and Hepatoprotective Effects of Three Olive Leave Species Cultivated in Aljouf Region, Saudi Arabia

Abstract: Aim of the work: the purpose of this study was to evaluate the antioxidant, anti-inflammatory and hepatoprotective effects of extract from 3 olive leave cultivars; K18, Nibali and Sorani growing in Aljouf region, Saudi Arabia. Methods: all plants were extracted with 80% methanol and the extracts were used to determine the total phenolic content, the total flavonoid content, the DPPH radical and anti-lipid peroxidation scavenging activities. In vivo hepatoprotective effect of these olive leaves extracts (OLEs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(26 reference statements)
1
1
0
Order By: Relevance
“…Compared to the PTL-administered group, pretreatment with OLE and silymarin reduced apoptotic events in the liver, as seen by lower hepatic CASP3 expression. Similar antiapoptotic effects of OLE and silymarin have been documented earlier (Osman and Tantawy 2017 , Teksoy et al 2020 ). Several bioactives in OLE and MLE have been known by their antiapoptotic activity.…”
Section: Discussionsupporting
confidence: 83%
“…Compared to the PTL-administered group, pretreatment with OLE and silymarin reduced apoptotic events in the liver, as seen by lower hepatic CASP3 expression. Similar antiapoptotic effects of OLE and silymarin have been documented earlier (Osman and Tantawy 2017 , Teksoy et al 2020 ). Several bioactives in OLE and MLE have been known by their antiapoptotic activity.…”
Section: Discussionsupporting
confidence: 83%
“… 27 reported that Olea europaea extract may lead to cell wall or cell membrane disruption to Gram-positive bacteria, which was more susceptible compared to Gram-negative bacteria. The antioxidant activity of Tanta LEM extract was 87.55% at concentration of 50 μg/ml which could be explained by Osman & Tantawy 28 who mentioned that olive leaves were considered as the highest scavenging activity radical of different parts of olive trees. The wound healing activity of Olea europaea can be explained by Rosa et al., 29 where olive oil administration proved to increase cell migration, TGF- β protein expression, and collagen deposition.…”
Section: Discussionmentioning
confidence: 91%